2015
DOI: 10.18287/jbpe-2015-1-2-98
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Optics and Photonics: Light-Tissue Interaction

Abstract: Abstract. This is the second section of the review-tutorial paper describing fundamentals of tissue optics and photonics. As the first section of the paper was mostly devoted to description of biological tissue structures and their specificity related to interactions with light [1], this section 3 describes light-tissue interactions themselves that are caused by tissue dispersion, scattering, and absorption properties, including light reflection and refraction, absorption, elastic, and quasi-elastic scattering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
152
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(170 citation statements)
references
References 38 publications
1
152
0
7
Order By: Relevance
“…In clinical studies the effectiveness of ischemic stroke treatment in humans was shown when initiated within 24 hours of stroke onset at the application of a hand-held 808-nm laser probe to twenty predetermined locations on the shaved scalp for 2 min in each location with the predicted power density of ∼10-15 mW/cm 2 on the dura mater. The light-induced regeneration of the crushed rat facial nerves was found to be the best for 633-nm laser with the dosage of 162.4 J/cm 2 comparing with the other wavelengths tested, such as 361, 457, 514, 720, and 1064 nm. Phototherapy can progressively improve nerve function, and can be used in patients with longterm peripheral nerve injury at 780-nm laser treatment.…”
Section: Low Level Light Therapy (Lllt)mentioning
confidence: 88%
See 3 more Smart Citations
“…In clinical studies the effectiveness of ischemic stroke treatment in humans was shown when initiated within 24 hours of stroke onset at the application of a hand-held 808-nm laser probe to twenty predetermined locations on the shaved scalp for 2 min in each location with the predicted power density of ∼10-15 mW/cm 2 on the dura mater. The light-induced regeneration of the crushed rat facial nerves was found to be the best for 633-nm laser with the dosage of 162.4 J/cm 2 comparing with the other wavelengths tested, such as 361, 457, 514, 720, and 1064 nm. Phototherapy can progressively improve nerve function, and can be used in patients with longterm peripheral nerve injury at 780-nm laser treatment.…”
Section: Low Level Light Therapy (Lllt)mentioning
confidence: 88%
“…where χ (2) is the second order nonlinear susceptibility, E(ω) and τ p are the laser pulse energy and width, respectively. As in two-photon fluorescence (see Eq.…”
Section: Second Harmonic Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Skin has a complex inhomogeneous structure causing a strong light scattering, which limits the optical methods applicability to the diagnostics and treatment of various diseases [1,2]. The development of methods enhancing the optical clearing of skin is an urgent problem that has been a subject of multiple studies [3,4].…”
Section: Introductionmentioning
confidence: 99%